Effects of Blended Fertilizer Rate and Time of Application on Growth and Yield of Sugarcane Ratoon Crop at Arjo-Sugar Factory, Western Ethiopia - Legesse, Dereje; Legesse, Hirpa; Geleta, Negash (Science, Technology and Arts Research Journal, 2016)
Lack of appropriate agronomic practices related to fertilizer management is a major constraint to enhancing sugarcane yield in Ethiopia. The effect of optimum rate and time of blended fertilizer application on yield and quality of ratoon commercial crop is not known at Arjo Didessa Sugar factory. Therefore, the field experiments were conducted with the objectives of assessing the effect of blended fertilizer at different rate and time of application on Ratoon sugarcane growth and yield of cane. The treatments consisted of eight levels of blended fertilizer with N (0, 150, 111N, 200 and 103N, 250 and 94N, 300 and 85N, 350 and 76.4N, 400 and 68N kg ha-1 and recommended fertilizer rate) and two times of application (one and two month after harvest). The field experiments were laid out as Randomized complete block design in a factorial arrangement and replicated three times. A sugarcane cultivar named N-14 was used as a ratoon material. Analysis of variance of the data revealed that the blended fertilizer application rate had significant effect on ratoon weight per stalk, node number, plant height, node length and cane yield sugar yield. Blended fertilizer rate and time of application and their interaction showed only highly significant on stalk girth and stalk population and interaction was significant effect on weight per stalk and node length at the time of harvest. However, application of blended fertilizer at different time and their interaction on plant height, cane yield and node number did not showed significant effect. Blended fertilizer treatment with the rate of 250kg ha-1 blended fertilizer mixed with 94kg N ha-1 at one month after harvest resulted in higher ratoon cane weight per stalk, stalk girth, cane yield, sugar yield, node length, stalk population and node number. Therefore, highest cane yield was recorded at late application time of blended fertilizer at lower dose and higher dose of nitrogen. Therefore, treating the ratoon cane by 250kg ha-1 BLF with 94kg N ha-1 at one month after harvest had evidently the advantage of improving ratoon cane growth and yield performance.